Solubility of Polysaccharides - Xu, Zhenbo (IntechOpen, 2017)
Sugars, with a scientific term as saccharides, are involved in various aspects in the lives of human beings, including the sense of taste, energy for daily life, etc. Recent development in polysaccharides, as well as the background knowledge in this field, further deepens insight into their roles as healthy supplements. In this book, the principles on polysaccharides' solubility and structure, methodologies and application of polysaccharides have been reviewed. The chapters in this book include the relationship between structure and solubility of polysaccharide, the experimental and computational researches on polysaccharide solubility and the common polysaccharide, which may further aid scholars and researchers in regard to solubility of polysaccharides, methodologies and modification.